Instrumental Analysis of Student Perceptions of Chemistry Learning with the STEM Approach at the end of the Covid-19 Pandemic using Second Order Confirmatory Factor Analysis - Anti Kolonial Prodjosantoso; Fajar Naqsyahbandi (Postgraduate, University of Mataram, 2023)
This study aims to prove the construct validity and reliability of students' perceptions of chemistry learning instruments using the STEM approach using Second Order Confirmatory Factor Analysis. The sample in this study was 455 public high school students spread across South Bengkulu district, Bengkulu Province. The instrument developed is a questionnaire instrument using a Likert scale which consists of four dimensions, namely the scientific dimension (DS), the mathematical dimension (DM), the engineering and technology dimension (DTT) and the STEM dimension (DST). The results of the study show that the four dimensions have good validity and are still acceptable because the loading factor value is above 0.40. In proving reliability using Cronbach's Alpha, a value of > 0.6 (0.855) was obtained so that it was declared reliable and in further analysis proving construct reliability using Composite Reliability (CR) showed that all dimensions of student perceptions had good construct reliability as well